Redukcja teorii a założenia strukturalne - Strawiński, Witold (Filozofia Nauki, 1995)
in the article different kinds of theory reduction are distinguished and discussed with respect to additional assumptions which are usually added to the reducing theory. A particular kind of so-called geometrical structural assumptions are analysed, and some outline of their possible classification is presented.